2018
DOI: 10.11591/edulearn.v12i3.8248
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Principal Leadership Style and Teacher Work Motivation on the Performance of Certified Teachers at SMA Negeri Kotamobagu, North Sulawesi, Indonesia

Abstract: The purpose of this study is to analyse and interpret the influence of principal leadership style on the performance of certified teachers, the influence of teacher work motivation on the performance of certified teachers and the influence of principal leadership style and teacher work motivation simultaneously on the performance of certified teachers in SMA Negeri Kotamobagu. This study employs a quantitative study approach with survey methods and multiple regression analysis techniques. The independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
1
8
0
3
Order By: Relevance
“…The results of this study are also supported by the subsequent: Taufiq et al 2016 Tambingon (2018) which revealed the results of the same research on the influence of leadership styles with teacher performance.…”
Section: The Influence Between Principal Leadership Styles On Teachersupporting
confidence: 87%
“…The results of this study are also supported by the subsequent: Taufiq et al 2016 Tambingon (2018) which revealed the results of the same research on the influence of leadership styles with teacher performance.…”
Section: The Influence Between Principal Leadership Styles On Teachersupporting
confidence: 87%
“…Teacher outlets include school ties and peer to peer in professional development efforts. Research (Tambingon, 2018) shows it is necessary. for the principal's need for expertise and desire to mobilize and be responsible to his subordinates (teachers) when carrying out school-based learning activities.…”
Section: Resultsmentioning
confidence: 99%
“…Ada pengaruh langsung motivasi kerja terhadap kinerja guru. Untuk mengatasi permasalahan kinerja guru yang berkaitan dengan masalah internal, diperlukan upaya dari instansi pendidikan, guru, dan kepala sekolah dengan mengubah kebijakan program untuk meningkatkan mutu pendidikan menjadi kepemimpinan yang efisien dan efektif, melaksanakan pelimpahan tugas yang berfokus pada proses pembelajaran dan hasil belajar siswa (Widiyanti et al, 2018 (Tambingon, 2018).…”
Section: Pendahuluanunclassified